Identitas nasional: peran budaya politik, demokrasi dan civil society - Septiana, Nur Ayu (Maliki Interdisciplinary Journal, 2025)
This study aims to analyze the meaning and essence of democracy, the development of democracy, the construction of civil society, and the implementation of the democratic system in the Unitary State of the Republic of Indonesia (NKRI). Using a literature review method and qualitative analysis, this journal examines the dynamics of Indonesian democracy from the period of independence to the reform era, as well as the role of civil society in strengthening democracy. The literature findings indicate that Indonesian democracy has undergone significant transformation through four main periods, while civil society plays a crucial role in safeguarding human rights and democratic values. The conclusion of this study emphasizes the importance of strengthening substantive democracy and civil society in realizing inclusive and equitable governance in Indonesia.